ANESTHESIA MANAGEMENT OF ESOPHAGEAL ATRESIA REPAIR SURGERY: A CASE REPORT - Putra, Kadek Agus Heryana; Kurniyanta, Putu; Wiryana, Made; Sinardja, Ketut; Senapathi, Tjokorda Gde Agung; Widnyana, I Made Gede; Cindryani, Marilaeta; Kurnia, Prajnaariayi Prawira (Bali Journal of Anesthesiology, 2018)
ABSTRACTEsophageal Atresia (EA)is a congenital anomaly commonly found with TracheoesophagealFistula (TEF) of neonates in the first week oflife. This anomaly can cause several complications includingaspiration, reduction in respiration, and other complication from other concomitant congenital anomaly, mostly from heart origin. The treatment for this anomaly is surgery.Intraoperatively, thepatient may develop hypoxia due to lung retraction and hemodynamic instability from bleeding or hypothermia. Anesthesiologists play important role in the management of EA during theperioperative period. Careful examination of the preoperative period must be done to discover any other concomitant anomaly and complication. Good anticipation of any complication during surgery and continuous monitoring post surgery can elevate the prognosis of the patient.